VARIABLE-COEFFICIENT BALANCING-ACT ALGORITHM EXTENDED TO A VARIABLE-COEFFICIENT MKP MODEL FOR THE ROTATING FLUIDS - GAO, YI-TIAN; TIAN, BO (International journal of modern physics. C, Computational physics, physical computation, 2001)
The modified Kadomtsev–Petviashvili (MKP) models describe the large-scale motion of such rotating fluids as the atmosphere and oceans. Based on the computerized symbolic computation, we in this paper extend the power of the variable-coefficient balancing-act method, which is recently proposed, to a variable-coefficient MKP model. The model is re-written as a coupled set of partial differential equations, and the algorithm is re-written correspondingly. We obtain a new family of the soliton-like, exact analytic solutions, beyond the traveling waves.